Evaluation of public management: Costa Rica Central Government period 2007-2017 - Carranza Villalobos, Carlos (2021)
Public investment contributes to understanding the economic growth’s level of a country, through active participation in strategic areas such as finance and economic policy. Taking into account that the Government has limited resources, the need arises for effective monitoring and evaluation processes of public investment projects both for the fulfillment of institutional goals and objectives, as well as to ensure transparency and efficient public resources use. In this sense, government authorities must have the conceptual and operational tools necessary in order to raise the proposal of strategic projects, as well as facilitate the exact identification of results through management indicators that allow decision makers to channel the relevant information linked to social priorities and the availability of resources. This article addresses the main findings on the study of the capacities of 10 Ministries of the Central Government of Costa Rica; through the collection and analysis of both qualitative and quantitative data to know the incidence of the projects executed by said entities for the construction of general well-being, accompanied by innovation and entrepreneurship of this public management.